STRATEGI FUNDRAISING DALAM MENGELOLA DANA (ZIS) ZAKAT, INFAQ, SHADAQAH DI LAZISMU WILAYAH BENGKULU - Agro Kurniawan; Sri Ekowati (UM. Bengkulu, 2022)
This research presents the study of fund-raising strategy for managing the funds of Zakat, Infaq, Shadaqah atMuhammadiyah Zakat, Infak, and Shodaqoh Institution (Lazismu)of Bengkulu Region. This study aims to determine the fund-raising strategy in managing Zakat, Infaq, Shadaqah funds at Lazismu. This type of research was descriptive by using qualitative methods. The method of data collection technique were through observation, interviews, and documentation.The results of this study indicated that the strategies of Lazismu generally used dialogue fund-raising, corporate, multi-channel and donor retention and development. There was no longer routinely for distributing ZIS, due to lack of public understanding in term of obligation to carry out ZIS. Keywords: Fund-raising Strategy, Dialogue, Corporate, Multi-channel, Develovment.